UNDERSTANDING THE MEANING OF HADITH AND THE SCIENCE OF HADITH ACCORDING TO WAHBAH ZUHAILI'S VIEWS - Reynia Lituhayu Zerlinda; Moh Randy Ferdiansyah; Ragil Adrian Fazqy Afriansyah; Shofil Fikri (INJOSEDU: International Journal of Social and Education, 2025)
In this study, our focus is to understand Wahbah Zuhaili's views on hadith and hadith science, relating them to the lives of Muslims. Hadith, as the source of Islamic law, is the center of attention as the words and deeds of the Prophet Muhammad SAW. Hadith, which studies the origin and criteria of hadith, is essential in the understanding of religion. This research is important because hadith and the science of hadith play a vital role in the lives of Muslims, including in the fields of law, ethics, and general view. Our research method involves the collection of literature and the analysis of Zuhaili's texts. Zuhaili's literature related to hadith and hadith science is compiled and analyzed to reveal his perspective. The results of the study show that Zuhaili emphasized the importance of hadith as a source of law that needs to be understood by Muslims, especially the younger generation. Hadith science, according to him, plays a key role in helping Muslims memorize, appreciate, and absorb the teachings of the hadith inherited by the Prophet Muhammad SAW.